2023
DOI: 10.3390/v15020406
|View full text |Cite
|
Sign up to set email alerts
|

Retracing Phylogenetic, Host and Geographic Origins of Coronaviruses with Coloured Genomic Bootstrap Barcodes: SARS-CoV and SARS-CoV-2 as Case Studies

Abstract: Phylogenetic trees of coronaviruses are difficult to interpret because they undergo frequent genomic recombination. Here, we propose a new method, coloured genomic bootstrap (CGB) barcodes, to highlight the polyphyletic origins of human sarbecoviruses and understand their host and geographic origins. The results indicate that SARS-CoV and SARS-CoV-2 contain genomic regions of mixed ancestry originating from horseshoe bat (Rhinolophus) viruses. First, different regions of SARS-CoV share exclusive ancestry with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…2-7). Such results were predictable as previous studies on sarbecoviruses have shown that their genomes evolve through frequent recombination 13,23, 24 , which means that different regions of a genome or gene alignment can bring multiple phylogenetic signals. To better summarize evolutionary relationships among sarbecoviruses, we have therefore chosen to perform phylogenetic analyses based on the sliding window bootstrap (SWB) and SuperTRI methods (Supplementary Table 5).…”
Section: Phylogenetic Treessupporting
confidence: 79%
See 4 more Smart Citations
“…2-7). Such results were predictable as previous studies on sarbecoviruses have shown that their genomes evolve through frequent recombination 13,23, 24 , which means that different regions of a genome or gene alignment can bring multiple phylogenetic signals. To better summarize evolutionary relationships among sarbecoviruses, we have therefore chosen to perform phylogenetic analyses based on the sliding window bootstrap (SWB) and SuperTRI methods (Supplementary Table 5).…”
Section: Phylogenetic Treessupporting
confidence: 79%
“…This approach was designed to reveal the phylogenetic relationships supported by the largest proportion(s) of the genome 13, 24 . The five SuperTRI bootstrap consensus (SB) trees reconstructed from the SWB analyses based on five window sizes (400, 500, 600, 1000, and 2000 nt) are available in Supplementary Fig.…”
Section: Phylogenetic Treesmentioning
confidence: 99%
See 3 more Smart Citations